2016
DOI: 10.3748/wjg.v22.i36.8123
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory bowel disease in India - Past, present and future

Abstract: There is rising incidence and prevalence of inflammatory bowel disease (IBD) in India topping the Southeast Asian (SEA) countries. The common genes implicated in disease pathogenesis in the West are not causal in Indian patients and the role of “hygiene hypothesis” is unclear. There appears to be a North-South divide with more ulcerative colitis (UC) in north and Crohn’s disease (CD) in south India. IBD in second generation Indian migrants to the West takes the early onset and more severe form of the West wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 93 publications
2
33
0
Order By: Relevance
“…4,14 This difference in distribution of UC and CD may be related to the differences in genetic heterogeneity, hygiene, and diet between the people of North and South India. 15,16 In our study as well, we found more UC cases than CD, and the proportion remained the same despite an increase in incidence in overall IBD. A recent study on 95 605 incident cases of CD and 112 004 incident cases of UC showed that the age of IBD onset varies with gender.…”
Section: Discussionsupporting
confidence: 77%
“…4,14 This difference in distribution of UC and CD may be related to the differences in genetic heterogeneity, hygiene, and diet between the people of North and South India. 15,16 In our study as well, we found more UC cases than CD, and the proportion remained the same despite an increase in incidence in overall IBD. A recent study on 95 605 incident cases of CD and 112 004 incident cases of UC showed that the age of IBD onset varies with gender.…”
Section: Discussionsupporting
confidence: 77%
“…UC is the most predominant type of IBD with a prevalence of 7.6 to 246.0 cases per 100000 per year, followed by CD which has a prevalence of 3.6 to 214.0 cases per 100000 per year[ 3 ]. The worldwide distribution of IBD is skewed towards being more prominent in North America and Europe, although in the past two decades its prevalence has risen in developing countries like China and India[ 4 , 5 ]. This change in trends has paralleled with changes in dietary habits like inclusion of processed foods, increased intake of sugars and fats, overutilization of antibiotics and an overall improvement in hygiene.…”
Section: Introductionmentioning
confidence: 99%
“…Ulcerative colitis (UC) and Crohn’s disease (CD) are two sub-types of IBD differing in few histological and pathological features. IBD occurrence in India tends to follow a north-south divide where UC and CD is predominant in north and south India respectively 1 . Incidence and prevalence rates of UC reported in India are the highest in Asia 2 .…”
Section: Introductionmentioning
confidence: 99%